Factors influence the level of staff turnover rate: A study among private nursing homes in Malaysia - Nurul Ashykin Abd Aziz; Hasif Rafidee Hasbollah; Nur A’mirah Mohd Yaziz; Mohd Asrul Hery Ibrahim (Medwell Journals, 2017)
This study aims to identified the factors that influence the level of staff turnover rate in private Nursing Home in Malaysia to improve staff and organisational effectiveness. Survey study in five Nursing Homes were conducted via questionnaire by asking the staffs to participate in this study. The results indicates that the factor that influence the level of staff turnover rate integrates: people which are qualified staff and development of attitude, skills, knowledge and performance for the effectiveness of service delivery; programme which include training and motivation programme, practical courses and job rotation as the practices; process, is the strategy of continuous improvement of people and programme in the Nursing Home; compensation, are the including the salary, incentives and financial benefit and job content, are covered the guidelines and work flow for the staffs whose working in private Nursing Home in Malaysia.